CXCR1/2 Antagonism Is Protective during Influenza and Post-Influenza Pneumococcal Infection - Tavares, Luciana P.; Garcia, Cristiana C.; Machado, Marina G.; Queiroz-Junior, Celso M.; Barthelemy, Adeline; Trottein, François; Siqueira, Marilda M.; Brandolini, Laura; Allegretti, Marcello; Machado, Alexandre M.; de Sousa, Lirlândia P.; Teixeira, Mauro M. (Frontiers in Immunology, 2017)
Rationale Influenza A infections are a leading cause of morbidity and mortality worldwide especially when associated with secondary pneumococcal infections. Inflammation is important to control pathogen proliferation but may also cause tissue injury and death. CXCR1/2 are chemokine receptors relevant for the recruitment of neutrophils. We investigated the role of CXCR1/2 during influenza, pneumococcal, and post-influenza pneumococcal infections. Methods Mice were infected with influenza A virus (IAV) or Streptococcus pneumoniae and then treated daily with the CXCR1/2 antagonist DF2162. To study secondary pneumococcal infection, mice were infected with a sublethal inoculum of IAV then infected with S. pneumoniae 14 days later. DF2162 was given in a therapeutic schedule from days 3 to 6 after influenza infection. Lethality, weight loss, inflammation, virus/bacteria counts, and lung injury were assessed. Results CXCL1 and CXCL2 were produced at high levels during IAV infection. DF2162 treatment decreased morbidity and this was associated with decreased infiltration of neutrophils in the lungs and reduced pulmonary damage and viral titers. During S. pneumoniae infection, DF2162 treatment decreased neutrophil recruitment, pulmonary damage, and lethality rates, without affecting bacteria burden. Therapeutic treatment with DF2162 during sublethal IAV infection reduced the morbidity associated with virus infection and also decreased the magnitude of inflammation, lung damage, and number of bacteria in the blood of mice subsequently infected with S. pneumoniae. Conclusion Modulation of the inflammatory response by blocking CXCR1/2 improves disease outcome during respiratory influenza and pneumococcal infections, without compromising the ability of the murine host to deal with infection. Altogether, inhibition of CXCR1/2 may be a valid therapeutic strategy for treating lung infections caused by these pathogens, especially controlling secondary bacterial infection after influenza.